The dossier 'Smako Skrijelj': The contribution to the study of the State Security Administration work in the area of Tutin and surrounding after the Second World War - Živković Milutin (Baština, 2012)
The activity of the Yugoslav Security Service due to its importance for the preservation of the newly established social set up, and evident controversies accompanying its work, attracts the attention of professional public opinion. Without any ambition to suggest eventual conclusions on the justification of the Administration of State Security working method from ideological aspect, this paper treats the case of the bodies of the Administration of State Security from Tutin for the outlaw Smako Skrijelj, which lasted almost two decades after the Second World War. Bearing in mind the fact this paper was written pursuant to the original archive material from the fund of Security-informative Agency, which is to be found in the Archive of Serbia, the versatility of method and way of working of the Yugoslav security service in our areas, being described following the case of Smako Skrijelj are raising numerous issues out of which some answers and conclusions will impose themselves.